Pengembangan Video Pembelajaran berbasis Filmora dan Quizizz Materi Mitigasi dan Adaptasi Kebencanaan di SMA Negeri 1 Bonepantai - Lowan Igirisa; Fitryane Lihawa; Rusiyah Rusiyah (Universitas Negeri Gorontalo, 2026)
The limited variety of geography instructional media at SMA Negeri 1 Bonepantai has led to difficulties among students in comprehending disaster mitigation and adaptation concept. In addition, the evaluation media employed by teachers have not yet been integrated with technology. This research aims to develop learning video media using Wondershare Filmora and Quizizz evaluation media on Disaster Mitigation and Adaptation material. This type of research is research and development ( RD). The development model applied is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research subjects consist of validation of materials, questions, media, and learning, product testing to class XP Students of SMA Negeri 1 Bonepantai of the material expert was 88.33%, question experts 81.66%, media experts 86.66%, and learning experts 91.42%. In accordance with the validation criteria, the value is categorized as very valid. The assessment of student responses, were 91.16% included very valid category. From the results of the student responses to the Wondershare Filmora learning video media was 90.88%, and for the Quizizz evaluation media, the student responses were 91,16%, which were included in the very valid category. It was concluded that the Wondershare Filmora-based learning video media and quizizz evaluation media, is very effective and feasible to be implemented.